The institute of attorney-client privilege (Polish experience) - Hrubinko , Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
This article provides an analysis of the legal framework for the institution of attorney-client privilege in Poland, indicating the situations when an attorney is entitled or obliged to disclose information covered by professional secrecy, as well as the consequences of an erroneous assessment of an attorney in such a situation. Some provisions requiring legislative amendments or functional interpretation in order to guarantee the observance of the attorney-client privilege in court proceedings are also considered.The study concludes that in Poland, the attorney-client privilege, known as professional secrecy, is a fundamental principle deeply rooted in legal ethics and professional conduct, which obliges lawyers to keep confidential all information obtained in the course of providing legal aid. Both lawyers and paralegals are bound by a legal obligation of confidentiality, which means that they cannot disclose communications received in the course of providing legal aid. Legislative changes are necessary in some cases, for example, when a lawyer should have the right to appeal against a court decision to disclose information constituting professional secrecy in relation to information obtained as a result of the operational and investigative activities of law enforcement agencies. In other cases, legislative amendments may not achieve their purpose, for example, to clarify certain topical issues. The Constitutional Court of Poland has also noted threats to the attorney-client privilege, for example, in the case of access to information constituting the attorney-client privilege by supervisory authorities exercising operational control. Despite the fact that there is a risk to the effective protection of professional secrecy, the court pointed out that it is the legislator who should introduce legal solutions that will prevent the risk of using information that needs to be protected, or at least minimise this risk, and that the possible misapplication of a provision in a particular case does not mean that it is unconstitutional.